2021
DOI: 10.1016/j.ygyno.2021.01.029
|View full text |Cite|
|
Sign up to set email alerts
|

Complete pathological response following levonorgestrel intrauterine device in clinically stage 1 endometrial adenocarcinoma: Results of a randomized clinical trial

Abstract: LNG-IUD is commonly used to treat patients with EHA or EAC. • Complete response rates were 43% and 82%, for EAC and EHA, respectively. • Pathological complete response was 61% for LNG-IUD alone.• Pathological complete response was 67% for LNG-IUD plus weight loss.• Pathological complete response was 57% for LNG-IUD plus metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 51 publications
3
60
0
Order By: Relevance
“…Knowing the role of obesity-related biological pathways and mediators in the pathogenesis and prognosis of endometrioid endometrial malignancies offers new perspectives and therapeutic strategies that have not been explored to date. A combined approach, comprising aromatase inhibitors combined with antidiabetic, anti-inflammatory, and antioxidant drugs, plus progestins administered locally through an intrauterine device [ 66 ], may constitute a new targeted therapeutic approach, particularly in women that, by virtue of obesity, may also have an increased risk of surgical complications and, therefore, could not receive optimal surgery. The contribution of targeting these pathways in the context of adjuvant treatment is no less important, where the information available is limited and scarcely homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the role of obesity-related biological pathways and mediators in the pathogenesis and prognosis of endometrioid endometrial malignancies offers new perspectives and therapeutic strategies that have not been explored to date. A combined approach, comprising aromatase inhibitors combined with antidiabetic, anti-inflammatory, and antioxidant drugs, plus progestins administered locally through an intrauterine device [ 66 ], may constitute a new targeted therapeutic approach, particularly in women that, by virtue of obesity, may also have an increased risk of surgical complications and, therefore, could not receive optimal surgery. The contribution of targeting these pathways in the context of adjuvant treatment is no less important, where the information available is limited and scarcely homogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…The feMMe trial enrolled patients with histologically confirmed, clinically stage 1 FIGO grade 1 EAC or EHA. The methods and primary outcomes of this study have been previously described ( Janda et al, 2021 ). Qualitative interviews were conducted as part of long-term follow-up of women who participated in the feMMe trial to inform the translation of the trial interventions into clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Only few clinical trials have evaluated the efficacy and oncologic safety of non-surgical treatment of EAC and EHA using levonorgestrel delivered by an intrauterine device (LNG-IUD) ( Hawkes et al, 2014 , Janda et al, 2021 , Kim et al, 2019 , Minig et al, 2011 , Westin et al, 2021 ), reporting pathological response rates ranging from 37% to 66% ( Janda et al, 2021 , Kim et al, 2019 , Minig et al, 2011 , Westin et al, 2021 ). One of these was the feMMe trial, a randomised controlled Phase II clinical trial that investigated the effectiveness of LNG-IUD for the treatment of EAC or EHA, with or without metformin or weight loss ( Janda et al, 2021 ). The feMMe trial enrolled 165 patients, 96 (58%) diagnosed with EAC and 69 (42%) diagnosed with EHA.…”
Section: Introductionmentioning
confidence: 99%
“…12 The evidence base for the use of the LNG-IUS when treating EEC appears promising, with treatment in this setting yielding response rates between 52% and 67%. [13][14][15][16] Compared with oral progestogens, the LNG-IUS has a similar disease regression rate and is associated with fewer systemic adverse effects due to being placed locally in the uterus. 17 Still, the evidence appears that there is inconsistency in response when using the LNG-IUS for treatment of early-stage EC in some women making the unknown mechanisms of LNG resistance a critical obstacle for the conservative management of EC.…”
Section: Introductionmentioning
confidence: 99%